2003
DOI: 10.1007/s10072-003-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurological abnormalities in adult celiac disease

Abstract: We assessed the occurrence of neurological signs and symptoms in adult patients with celiac disease and evaluated the correlation between neurological features and diet. A total of 176 patients and 52 age-matched controls underwent a semistructural interview and a neurologic examination. The effect of gluten-free diet was evaluated by comparing the prevalence of signs and symptoms among patients adhering to a gluten-free diet and patients on an unrestricted diet. The occurrence of headache, dysthymia and signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 20 publications
2
102
0
3
Order By: Relevance
“…After every reflux, there is a peristaltic wave in oesophagus which clears the gastric contents (16,33) . Almost 20% of adults complain of atleast 1 episode of heartburn/week and about 10% of them complain of daily episode of heartburn due to various trigerring factors mainly stress and sedentary lifestyle (8,14,45) .…”
Section: Discussion and Conclusion:-mentioning
confidence: 99%
“…After every reflux, there is a peristaltic wave in oesophagus which clears the gastric contents (16,33) . Almost 20% of adults complain of atleast 1 episode of heartburn/week and about 10% of them complain of daily episode of heartburn due to various trigerring factors mainly stress and sedentary lifestyle (8,14,45) .…”
Section: Discussion and Conclusion:-mentioning
confidence: 99%
“…Carta et al [73] found a significantly higher number of CD patients met the criteria for lifetime and 6-month major depressive disorder and panic disorder compared to controls. Other studies have reported higher rates of social phobia [74], anxiety [75,76], depression [74,77,78], and dysthymia [45]. A metaanalysis on anxiety and depression in CD found that depression is more common and more severe in adults with CD compared to normal controls.…”
Section: Depression and Anxietymentioning
confidence: 97%
“…Peripheral neuropathy is the second most frequent neurologic complication in CD patients [44] and has been reported in up to 50% of cases [28,45]. Cooke and Smith [34] reported that among 16 CD patients, neuropathy was the main cause of death in 4 patients and a significant contributing factor in another 4.…”
Section: Neuropathymentioning
confidence: 99%
“…8 Headaches, paresthesia, hyporeflexia, weakness, and vibratory sense reduction were reported to be more prevalent in CD patients vs controls. 9 These same symptoms were more prevalent in CD patients who did not strictly follow a GFD vs those who were compliant with GFD.…”
Section: Introductionmentioning
confidence: 92%